How to have a beer - Gaston, Nicola (New Zealand Science Review, 2017)
​The Awa Press Ginger Series books, themed around the idea of introducing ‘how to ...’ engage in various pastimes, are perhaps an unlikely venue for science communication. I started reading How to have a beer out of simple curiosity, sparked in part by the apparent novelty of a woman daring to flaunt her credentials as a beer expert in public, but went away musing on how interesting it is to see scientific knowledge being communicated in such a low key, but generally useful way. The topic lends itself to a variety of glimpses of science, to be sure – from mentioning Pasteur’s discovery of yeast, to discussing the various consequences bacteria can have in brewing, to dismissal of marketing claims of ‘contains only 2.5 carbohydrates’ as not involving valid units of measurement. There’s a lot in here for scientists to like, but perhaps most of all is the validation of scientific experimentation as a way to learn: the background to the book, after all, was Galletly’s experiment in tasting and blogging about 365 beers in a year, with both successes and failures accounted for along the way. For all that I enjoyed the diversions into science along the way, how-ever, this is not really a scientific book. But it is a form of dissemination of expertise that is deeply valuable, and successful in its goal of increasing the accessibility of a significant cultural phenomenon – the rise of craft beer – to everyone. It contains lessons on the value of continuing to learn, such as when Galletly acknowledges that “at first it felt good to make these strong sweeping statements about what I did and didn’t like’, a welcome note of nuance in a world in which expertise and authority are words too often used interchangeably, with no thought for the validity of personal experience. It’s also delivered with generous good humour and style, from the discussion of the modern relevance of medieval food safety laws, to the outdated assumptions behind the ‘pink it and shrink it’ approach of marketing beer to women. It’s a fun read.